Impact of fertigation frequency on growth and yield parameters of baby corn (Zea mays) under drip irrigation - KUMAR, MUKESH; RAJPUT, T B S; PATEL, NEELAM (The Indian Journal of Agricultural Sciences, 2015)
The experiments were conducted at the research farm of Water Technology Centre, Indian Agricultural Research Institute, New Delhi during 2010–2011 for three consecutive seasons (October 2010- February 2011, April- July 2011 and August- November 2011) to study the impact of different fertigation frequencies and dripper discharge at different system operating pressures on growth parameters, corn yield and fodder yield of baby corn (Zea mays L.) crop. The study was planned with nine treatments which included dripper discharges at three system operating pressures(0.5 kg/cm2, 1.0 kg/cm2 and 1.5 kg/cm2) and three fertigation frequencies (biweekly, weekly and fortnightly). Growth parameters, viz. number of leaves per plant, plant girth, plant height, leaf area and Leaf Area Index (LAI) of baby corn during different growth stages were measured and recorded. There was a significant (P